Magneto-dieletric properties of bismuth substituted barium hexaferrite - Ridgway, Leah M. (2011)
The work contained within this thesis seeks to address the dielectric and magnetic properties of bismuth substituted barium hexaferrite (composition BaBixFe12-xO19 where x = 0.0, 0.2, 0.5, 0.8, 1.0 and 1.5) across a broad frequency spectrum. This material is potentially of interest in antenna applications (specifically a dielectric resonator antenna) where high permittivity and permeability materials can be exploited to physically minimize the size of antenna devices.